2019
DOI: 10.3390/diagnostics9020055
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors in Ovarian Cancer: The Route to “Ithaca”

Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors are a novel class of therapeutic agents that target tumors with deficiencies in the homologous recombination DNA repair pathway. Genomic instability characterizes high-grade serous ovarian cancer (HGSOC), with one half of all tumors displaying defects in the important DNA repair pathway of homologous recombination. Early studies have shown significant efficacy for PARP inhibitors in patients with germline breast related cancer antigens 1 and 2 (BRCA1/2) mutations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 116 publications
(139 reference statements)
0
71
0
2
Order By: Relevance
“…PARP inhibitors have been combined with chemotherapy based on the fact that they block BER, and consequently may potentiate the efficacy of cytotoxins [104]. A major concern for this therapeutic strategy is the high risk of overlapping myelotoxicity; for this reason, initiation of standard chemotherapy doses has been accompanied by dose escalation of the PARP inhibitor.…”
Section: Talazoparib Combination Therapiesmentioning
confidence: 99%
“…PARP inhibitors have been combined with chemotherapy based on the fact that they block BER, and consequently may potentiate the efficacy of cytotoxins [104]. A major concern for this therapeutic strategy is the high risk of overlapping myelotoxicity; for this reason, initiation of standard chemotherapy doses has been accompanied by dose escalation of the PARP inhibitor.…”
Section: Talazoparib Combination Therapiesmentioning
confidence: 99%
“…Thus, PI3K/AKT targeting by PI3K inhibitors may be potential therapeutic implications for TNBC patients with BRCA mutations or HR deficiency. However, further molecular investigations are needed to identify the efficacy of LY294002 in DNA repair mechanisms including HR, non-homologous end-joining (NHEJ), microhomology-mediated end-joining (MMEJ), alternative NHEJ (alt-NHEJ), synthetic lethality, "BRCAness", and the Fanconi anemia signaling network (39).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of this discovery, the majority of breast cancers occur in women who lack germline mutations; increasingly, epigenetic alterations are being implicated in breast cancer initiation and progression. Study of the potential link between breast cancer and epigenetics is just beginning [20].…”
Section: Epigenetic Changes Associated With Breast Cancermentioning
confidence: 99%
“…The epigenetic inactivation of BRCA1/2: Homologous recombination deficiency can result from epigenetic processes, leading to the silencing of homologous recombination genes, including BRCA1/2 [21]. Early studies have shown significant efficacy for PARP inhibitors in patients with BRCA1/2 mutations [20]. It is not clear whether the biological effects of harboring somatic BRCA1/2 mutations are identical to their germline counterparts (BRCAness phenomenon) [21].…”
Section: Epigenetic Changes Associated With Breast Cancermentioning
confidence: 99%